Characterization of amphotericin B liposome formulations - Manosroi A. (2014)
Liposomes composed of hydrogenated soya phosphatidylcholine (Emulmetik 950®)/cholesterol/charged lipids [dicetyl phosphate (-) or stearylamine (+)] were developed. The hydrogenated soya phosphatidylcholine/cholesterol/charged lipid liposomes at molar ratios of 1:1:0, 7:2:0, 7:2:1 (-), and 7:2:1 (+), with and without the entrapped amphotericin B (0.05 mg AmB/mg lipid), were prepared by a chloroform-film method with sonication. The charges of liposomes were characterized by a Zeta-Meter. The negative liposomes with and without the entrapped AmB showed higher surface charge density than other formulations. The size distribution of liposomes determined by standard error of the mean (SEM) was in the range of 0.115 to 0.364 μm. The smallest size was observed in the negative liposomes with the entrapped drug [7:2:1 (-) AmB]. The lamellarity of more than 15 layers was observed by transmission electron microscope (TEM) in the neutral liposomes with the entrapped drug [7:2 AmB]. The transition temperature and enthalpy of transition (ΔH) were determined by differential scanning calorimetry (DSC). Positive liposomes with the entrapped and unentrapped AmB demonstrated higher ΔH of the first peak than other formulations, indicating higher rigidity of liposomal membrane. The AmB contents in liposomes were determined by high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection at 382 nm. The percentages of entrapment of AmB in all formulations were above 85%. The positive liposome [7:2:1 (+) AmB] formulation, which gave the highest thermal stability, was selected for further skin absorption evaluation.